Temperature Analysis When Using Ethylene-Glycol-Based TiO2 as a New Coolant for Milling - M., Yogeswaran; K., Kadirgama; M. M., Rahman; D., Ramasamy (Universiti Malaysia Pahang, 2015)
This paper presents the effects of various milling conditions on the tool wear and workpiece temperature when using ethylene-glycol-based TiO2 nanofluid as the coolant for stainless steel AISI 304. A TiN coated carbide insert is used as the milling tool. A thermocouple was embedded into the workpiece to record the workpiece temperature during the end-milling process. It can be clearly seen that the temperature keeps on increasing after each experimental pass for three sets of experiments. The experiment conducted using the ethylene-glycol-based TiO2 nanocoolant exhibits a much lower workpiece temperature compared to the experiment conducted using a normal commercial coolant. Milling with the ethylene-glycol-based TiO2 nanocoolant reduced the wear on the edge of the insert compared to the normal commercial coolant. In conclusion, end-milling stainless steel AISI 304 using a TiN coated carbide insert and an ethylene-glycol-based TiO2 nanocoolant exhibits superior results with regard to workpiece temperature and tool wear. The temperature was reduced by 30 percent when using the nanofluid.